Damper cage loss reduction and no-load voltage THD improvements in salient-pole synchronous generators - Nuzzo, Stefano; Galea, Michael; Gerada, C.; Gerada, David; Mebarki, Abdelslam; Brown, N.L. (2016)
Salient-pole synchronous generators (SG) have a long history of utilization as reliable power generation systems. Important aspects of such generators include a high power-to-weight ratio, high efficiency and a low cost per kVA output [1]. Another critical aspect is the requirement for very low harmonic content in the output voltage. Hence, it is very important to be able to model and predict the no-load voltage waveform in an accurate manner in order to be able to satisfy standards requirements, such as the permissible total harmonic distortion (THD). Also, at steady-state conditions, parasitic voltages are induced in the damper bars which lead to a current flow with associated power losses and an increase in temperatures. This paper deals with an in-detail analysis of a 4 MVA SG, whose operation is studied and compared with experimental results for validation purposes. The same platform is then used to propose innovative solutions to the existing design and operational challenges of the machine aimed at reducing ohmic loss in the damper cage and improving the output voltage THD, without reverting to disruptive techniques such as rotor and/or stator skewing.